Design, synthesis and biological Evaluation of novel chromones having 3,4-dihydropyrimidin-2(1H)-one core at C-8 in combination with triazoles: New α-glucosidase inhibitors and anti-bacterial agents - Kumara Swamy Taviti; T.B. Patrudu; Nagalakshmi Jeedimalla; Naresh Kumar Katari; Satyanarayana Yatam; Rambabu Gundla (European Journal of Medicinal Chemistry Reports)
The Biginelli reaction synthesizes dihydropyrimidones through a multi-component reaction. A β-ketoester, aldehyde, and urea or thiourea react in the presence of an acid catalyst to form these dihydropyrimidones. 3,4-Dihydropyrimidin-2(1H)-One/Chromone/Triazole hybrids (9a-9l) were synthesized by multiple steps including one pot Biginelli multicomponent reaction depicted in the scheme. An efficient method for the Biginelli reaction of Chromone aldehyde, acetoacetate esters, and urea employed in the presence of ferric chloride is described. In the end, we have successfully synthesized twelve derivatives of 3,4-Dihydropyrimidin-2(1H)-One/Chromone/Triazole hybrids and subjected them to testing for Antibacterial activity and α-glucosidase inhibition activity. Among these derivatives, compound 9g (IC50 = 142.92 nmol) and 9e (144.49 nmol) exhibited significant inhibitory activity in comparison to the positive control acarbose (IC50 = 350.91 nmol). Compound 9g demonstrated the most significant suppression against Escherichia coli and Bacillus cereus, with zone diameters of 8.8 ± 1.35 mm and 9.1 ± 0.23 mm, respectively. Compound 9b displayed a clear area where bacterial growth was inhibited, measuring 7.5 ± 1.25 mm against Klebsiella pneumonia. Compound 9k exhibited a zone of inhibition measuring 8 ± 1.2 mm in radius against Staphylococcus epidermidis. The docking results for the synthesized compounds indicate that compound 9b exhibited the most favorable docking score of −10 kcal/mol, whereas compound 9a had the second-best docking score of −8.7 kcal/mol. Molecular docking was utilized to examine the interactions between the title compounds and α-glucosidase, in order to provide valuable insights. The data obtained revealed significant interactions that contribute to the inhibitory effects of the drugs against α-glucosidase. These compounds exhibit significant potential as attractive initial candidates for the development of new α-glucosidase inhibitors.